KEMAMPUAN MERANGKUM ISI BERITA MELALUI PEMANFAATAN MEDIA AUDIOVISUAL SISWA KELAS X SMAN 1 SEPUTIH BANYAK TP 2011/2012 - desi susanti; ni nyoman wetty suliani; wini tarmini (FKIP Universitas Lampung, 2013)
The problem in this research is the ability of summarizing news through the using of audiovisual media at the first grade of SMAN 1 Seputih Banyak in Academic year of 2011/2012. This research uses descriptive method. Population in this research is all students in the first grade of SMAN 1 Seputih Banyak in academic year 2011/2012. It consists of 244 students spreader in eight classes. The sample is taken about 15% from the number of each class so it is gotten 36 students. The collecting data is conducted by test technique. The conclusion is the ability of summarizing news through the using of audiovisual media at the first grade of SMAN 1 Seputih Banyak in Academic year of 2011/2012 belong to good criteria in which the average score is 72, 10. It is significant if it is compared by the research is conducting that is the students are active in doing sequences activities which is suitable to the purpose of the research.Key Word : Ability, summarizing, news, audiovisual media.